2018
DOI: 10.1089/fpd.2017.2350
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringensContamination in Retail Meat and Meat-Based Products in Bursa, Turkey

Abstract: This study examined the incidence of Clostridium perfringens in raw, ready-to-cook (RTC), and ready-to-eat (RTE) meat and meat-based products (N = 306) collected from restaurants, supermarkets, and butcher shops in Bursa, Turkey. In addition, we investigated the presence of the C. perfringens enterotoxin (CPE), as well as cpe genes and their source (chromosomal or plasmid borne). In this study, tryptose sulfite cycloserine (TSC) agar for classic culture isolation and API and real-time polymerase chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Similarly, previous studies found that all C. perfringens isolates from meat samples were positive for cap + gene [38,39], suggesting that it might be a universal gene in C. perfringens isolated from meat samples [40]. Moreover, the cpe + gene has been detected in 1.4% [25], 5% [41], and 27.2% [42] of C. perfringens isolated from raw and processed meats. In contrast, a recent study did not find cpe + gene in any of the C. perfringens isolates recovered from meat samples in Korea [32].…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, previous studies found that all C. perfringens isolates from meat samples were positive for cap + gene [38,39], suggesting that it might be a universal gene in C. perfringens isolated from meat samples [40]. Moreover, the cpe + gene has been detected in 1.4% [25], 5% [41], and 27.2% [42] of C. perfringens isolated from raw and processed meats. In contrast, a recent study did not find cpe + gene in any of the C. perfringens isolates recovered from meat samples in Korea [32].…”
Section: Discussionsupporting
confidence: 55%
“…Since the 1940s, food poisoning caused by the contamination of C. perfringens has been reported ( Yibar et al., 2018 ). The contamination rate of C. perfringens in retail meat products from different regions is different; for example, the contamination rate of C. perfringens in chicken products of this study is 51.11%, which is higher than the results of retail chicken meat samples in central China (15.1%) (Zhang et al., 2018 ), Korea (19.0%) (Jang et al., 2020 ) and the United States (30.00%) (Lin et al., 2003 ), and lower than the positive rate of Canadian retail chickens (67%) (Nowell et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Colony identification was confirmed by PCR assay based on the detection of the C. perfringens 16S rDNA gene, and the enumeration results were expressed in CFU/ml. 24 DNA extraction DNA extraction was performed using the boiling method. For this purpose, two bacterial colonies were placed inside a tube containing 50 μl of distilled water and boiled at 100°C for 10 min in a water bath.…”
Section: Isolation Of C Perfringensmentioning
confidence: 99%